Impact of meteorological conditions, canopy shading and leaf removal on yield, must quality, and norisoprenoid compounds content in Franciacorta sparkling wine - Ghiglieno, Isabella; Carlin, Silvia; Cola, Gabriele; Vrhovsek, Urska; Valenti, Leonardo; Garcia-Aloy, Mar; Mattivi, Fulvio (Frontiers in Plant Science, 2023)
Climate change is a major concern in agriculture; in grape wine production, climate change can affect yield and wine quality as they depend on the complex interactions between weather, plant material, and viticultural techniques. Wine characteristics are strongly influenced by microclimate of the canopy affecting primary and secondary metabolites of the vine. Air temperature and water availability can influence sugar and acid concentration in grapes and wines, and the synthesis of volatile compounds such as norisoprenoids. This becomes relevant in sparkling wine production where grapes are generally harvested at a relatively low pH, high acidity, and low sugar content and where the norisoprenoids significantly contributes to the final aroma of the wine. The effect of climate change on grape and wine, therefore, calls for the implementation of on-field adaptation strategies. Among them canopy management through leaf removal and shading have been largely investigated in the wine growing sector. The present study, conducted over 4 years (2010-2013) aims at analyzing how leaf removal and artificial shading strategies affect grape maturation, must quality and the production of some norisoprenoids in wine. Specifically, this paper investigates the effect of meteorological conditions (i.e., water availability and temperatures) and the effect of leaf removal and shading on Vitis vinifera L. cv. Chardonnay and Pinot noir, which are suitable to produce sparkling wine in the DOCG Franciacorta wine growing area (Lombardy, Italy). The effect of meteorological conditions and leaf removal and shading practices on norisoprenoids shall be the focus of the study. No defoliation and artificial shading treatments play an important role in the preservation of the acidity in warmer seasons and this suggests calibrating defoliation activities in relation to the meteorological trend without standardised procedures. This is particularly relevant in the case of sparkling wine, where the acidity is essential to determine wine quality. The enhanced norisoprenoid aromas obtained with a total defoliation represent a further element to direct defoliation and shading strategies. The obtained results increase knowledge about the effect of different defoliation and artificial shading applications in relation to meteorological condition supporting the management decision-making in the Franciacorta wine growing area.